2016
DOI: 10.1073/pnas.1523145113
|View full text |Cite
|
Sign up to set email alerts
|

PtdIns(4,5)P 2 signaling regulates ATG14 and autophagy

Abstract: Autophagy is a regulated self-digestion pathway with fundamental roles in cell homeostasis and diseases. Autophagy is regulated by coordinated actions of a series of autophagy-related (ATG) proteins. The Barkor/ATG14(L)-VPS34 (a class III phosphatidylinositol 3-kinase) complex and its product phosphatidylinositol 3-phosphate [PtdIns(3)P] play key roles in autophagy initiation. ATG14 contains a C-terminal Barkor/ATG14(L) autophagosome-targeting sequence (BATS) domain that senses the curvature of PtdIns(3)P-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 39 publications
1
64
0
Order By: Relevance
“…Although these studies suggested a direct role of PI4P or the PI4K2A protein itself in the control of these trafficking steps, several studies have shown that PI(4,5)P 2 also controls lysosomal degradation of integral membrane proteins (Sun et al , ; Schill et al , ; Tan et al , ). PI(4,5)P 2 was found to regulate autophagy initiation (Tan et al , ) and lysosome reformation from autophagosomes (Rong et al , ). The Tan study has established a physical connection between the PIP5Kγ i5 isoform and the ATG14 protein and showed that PI(4,5)P 2 binding to the C‐terminal Barkor/ATG14(L) autophagosome‐targeting sequence of ATG14 promotes its assembly with Vps34 and Beclin1 and hence is critical for autophagosome initiation (Tan et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies suggested a direct role of PI4P or the PI4K2A protein itself in the control of these trafficking steps, several studies have shown that PI(4,5)P 2 also controls lysosomal degradation of integral membrane proteins (Sun et al , ; Schill et al , ; Tan et al , ). PI(4,5)P 2 was found to regulate autophagy initiation (Tan et al , ) and lysosome reformation from autophagosomes (Rong et al , ). The Tan study has established a physical connection between the PIP5Kγ i5 isoform and the ATG14 protein and showed that PI(4,5)P 2 binding to the C‐terminal Barkor/ATG14(L) autophagosome‐targeting sequence of ATG14 promotes its assembly with Vps34 and Beclin1 and hence is critical for autophagosome initiation (Tan et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Not clear is the question as to what extent PI4P acts on its own right or can be converted to PI(4,5)P 2 in endocytic compartments to regulate these events. Recent studies showed specific forms of PIP5Kγ in the control of ATG14 and autophagy flux (Tan et al , ) and also in regulating lysosomal degradation of e‐cadherin (Schill et al , ) or the EGF receptor (Sun et al , ). Yet, some other studies suggested that PI4P regulates autophagy unrelated to PI(4,5)P 2 production (Wang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of autophagy has been found to promote resistance and survival of cancer cells treated with EGFR kinase inhibitors (Tan et al ., ). The mechanism seems to resemble the one induced by LAPTM4B in the physiological context.…”
Section: Noncanonical Kinase‐dependent and Kinase‐independent Egfr Fumentioning
confidence: 97%
“…This provides a means to localize membrane binding proteins to particular compartments on the basis of electrostatics, lipid packing, and local geometry. Phosphoinositides (PI) in particular, seem to have an emerging role in regulating cellular processes where micron-scale curvature is present including forespore membrane extension in S. pombe [57], autophagy [100], and micropinocytosis [101] in mammalian cells. Septins may be locally recruited to membranes based on the local lipid composition.…”
Section: Regulation Of Micron-scale Curvature Sensorsmentioning
confidence: 99%